The first record of Dendrothrips aspersus (Thysanoptera: Thripidae) from Iran - K. Minaei (Journal of Entomological and Acarological Research, 2015)
The species Dendrothrips aspersus Bhatti, 1971 is reported for the first time from Iran, based on the materials collected on grasses. This species was endemic to their originated region and is recorded for the first time outside their native range. The host records of D. aspersus in both India and Iran are discussed. Moreover, the number of thrips species that have been recently recorded from Iran are tabulated.